2011
DOI: 10.1111/j.1365-3016.2011.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing prospective cohort studies for assessing reproductive and developmental toxicity during sensitive windows of human reproduction and development – the LIFE Study

Abstract: Summary Buck Louis GM, Schisterman EF, Sweeney AM, Wilcosky TC, Gore-Langton RE, Lynch CD, Boyd Barr D, Schrader SM, Kim S, Chen Z, Sundaram R, on behalf of the LIFE Study. Designing prospective cohort studies for assessing reproductive and developmental toxicity during sensitive windows of human reproduction and development – the LIFE Study. Paediatric and Perinatal Epidemiology 2011; 25: 413–424. The relationship between the environment and human fecundity and fertility remains virtually unstudied from a cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 23 publications
2
121
0
Order By: Relevance
“…Further details on the study design are provided elsewhere. 24 Following enrollment, couples were followed daily until a positive home pregnancy test or 12 months of trying. To be inclusive of the wide range of couples attempting pregnancy, only couples in which at least one partner had been told they would require medical assistance to become pregnant were excluded.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the study design are provided elsewhere. 24 Following enrollment, couples were followed daily until a positive home pregnancy test or 12 months of trying. To be inclusive of the wide range of couples attempting pregnancy, only couples in which at least one partner had been told they would require medical assistance to become pregnant were excluded.…”
Section: Study Populationmentioning
confidence: 99%
“…Together, the data from the fertility monitor and the daily diaries were used to define menstrual cycles used for determining TTP. 24 Women were provided with highly sensitive (25 IU/L) home pregnancy tests 25 that provide digital readouts of "pregnant" and "not pregnant" to ensure accuracy reading results 26 and were instructed to begin testing on the day of expected menses. A single positive pregnancy test denoted an human chorionic gonadotropin pregnancy.…”
Section: Outcome Ascertainmentmentioning
confidence: 99%
“…Moreover, based on our results, 16% of infertile women have mentioned extreme dependency to nicotine, while none of the fertile women reported extreme dependency to nicotine. A laboratory study analyzed the impact of the different concentrations of nicotine on fertility in rats and showed that nicotine had a dose-dependent effect on fertility power (Louis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…According to one study, tobacco use likely increases infertility by 1.6-fold (Hatch et al, 2006). Berthiller and colleagues, however, reported that fertility did not decline in both male and female passive smokers (Louis et al, 2011;Oyeyipo et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…We felt this choice was justified as conception delay has been empirically shown to be a very good marker of identifying which couples will need clinical evaluation and/or treatment. While there have only been a few studies that have followed couples from discontinuing contraception through 12 months of trying, the data demonstrate that 76–90% of couples who do become pregnant do so within the first 6 months of trying (Gnoth et al ., 2003; Wang et al ., 2003; Buck Louis et al ., 2009, 2011). Moreover, clinical guidance suggests that couples seek care if not pregnant within 6 months of trying when the female partner is 35+ years of age.…”
Section: Discussionmentioning
confidence: 99%